Evaluation of the Mandarin Fricative-Affricate (MFA) nonsense word test training module among audiologists and audiology students - Valencia Ling Ling Bong; Foong Yen Chong; Rafidah Mazlan; Nashrah Maamor (Penerbit Universiti Kebangsaan Malaysia, 2025)
The Mandarin Fricative-Affricate (MFA) Nonsense Word Test was developed to assess the speech perception of Malaysian Mandarin-speaking adult clients. However, the language barrier makes it difficult for the audiologists and the audiology students who do not speak Mandarin to administer the test. Therefore, this study aimed to develop and evaluate a training module for the MFA Nonsense Word Test and measure the changes in confidence and perception of audiology students towards administering the MFA Nonsense Word Test. The training module consisted of (1) self-learning using a user manual and seven training videos and (2) practical sessions. This study consisted of two phases: (1) content validation of the user manual, and (2) workshop training. Six audiologists were involved in Phase I. The adapted Suitability Assessment of Materials (SAM) was used to measure the content validation of the user manual. The user manual was proven valid with an excellent content validity index (CVI) of 0.83. Thirty four audiology students participated in Phase II. The questionnaire for assessing the confidence and perception of the participants toward administering the MFA Nonsense Word Test was distributed at three time points: pre-workshop, pre-practical, and post-workshop. The participants were also required to evaluate the face validity of the training videos using the Patient’s Education Materials Assessment Tool (PEMAT). The training videos obtained a high face validity score of 98.7%. Friedman’s Test showed that there were significant changes in confidence [χ2 (2)=51.74, p<0.05] and perception [χ2 (2)=48.59, p<0.05] over the three time points. The finding indicated that the training module has effectively improved the audiology students’ confidence and perception in administering the MFA Nonsense Word Test.